2017
DOI: 10.1523/eneuro.0198-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1R Signaling Directly Activates Arcuate Nucleus Kisspeptin Action in Brain Slices but Does not Rescue Luteinizing Hormone Inhibition in Ovariectomized Mice During Negative Energy Balance

Abstract: Kisspeptin (Kiss1) neurons in the hypothalamic arcuate nucleus (ARC) are key components of the hypothalamic-pituitary-gonadal axis, as they regulate the basal pulsatile release of gonadotropin releasing hormone (GnRH). ARC Kiss1 action is dependent on energy status, and unmasking metabolic factors responsible for modulating ARC Kiss1 neurons is of great importance. One possible factor is glucagon-like peptide 1 (GLP-1), an anorexigenic neuropeptide produced by brainstem preproglucagon neurons. Because GLP fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 65 publications
1
32
1
Order By: Relevance
“…33 The gut hormones, GLP-1, PYY and glucagon have key roles in glucose homeostasis. Additionally, in rodent studies, GLP-1 has been shown to alter hypothalamic kisspeptin expression and neuronal activity, 42,43 and in mice glucagon stimulates hepatic kisspeptin production to alter GSIS. 13 In our study, there was no difference in circulating GLP-1, PYY or glucagon levels following intravenous glucose during kisspeptin administration compared to vehicle ( Figure S1C-E).…”
Section: Discussionmentioning
confidence: 99%
“…33 The gut hormones, GLP-1, PYY and glucagon have key roles in glucose homeostasis. Additionally, in rodent studies, GLP-1 has been shown to alter hypothalamic kisspeptin expression and neuronal activity, 42,43 and in mice glucagon stimulates hepatic kisspeptin production to alter GSIS. 13 In our study, there was no difference in circulating GLP-1, PYY or glucagon levels following intravenous glucose during kisspeptin administration compared to vehicle ( Figure S1C-E).…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1R agonist also results in a direct membrane depolarization of ARC KP cells. However, central infusions of the GLP-1R antagonist, exendin (9–39), did not exert any effect on expression of ARC Kiss1mRNA or plasma LH in the normal fed mice ( 128 ).…”
Section: Mechanism Of Metabolic Impact On the Hypothalamic Kp Systemmentioning
confidence: 97%
“…Heppner et al ( 128 ) reported that KP neurons in the hypothalamic ARC receive synaptic input from glucagon-like peptide 1 (GLP-1), which is an anorexigenic neuropeptide. Moreover, KP neurons also express Glp1r mRNA.…”
Section: Mechanism Of Metabolic Impact On the Hypothalamic Kp Systemmentioning
confidence: 99%
“…They are not neuropeptide Y/agouti‐related peptide or parvalbumin positive, although they may include a population of GABAergic interneurones . Interestingly, kisspeptin neurones in this nucleus were recently shown to express GLP1R mRNA and directly respond to GLP1 . Although these neurones are unlikely to be directly involved in metabolic regulation, they are known to be highly influenced by information about nutrient availability .…”
Section: Discussionmentioning
confidence: 99%
“…34 Interestingly, kisspeptin neurones in this nucleus were recently shown to express GLP1R mRNA and directly respond to GLP1. 35 Although these neurones are unlikely to be directly involved in metabolic regulation, they are known to be highly influenced by information about nutrient availability. 36,37 Similarly, the neurochemical identity of GLP1R-expressing neurones in the PVN and DMH remains to be determined 32 .…”
Section: Discussionmentioning
confidence: 99%